2022
DOI: 10.3390/ijerph19063605
|View full text |Cite
|
Sign up to set email alerts
|

No Excess Mortality up to 10 Years in Early Stages of Breast Cancer in Women Adherent to Oral Endocrine Therapy: A Probabilistic Graphical Modeling Approach

Abstract: Breast cancer (BC) is globally the most frequent cancer in women. Adherence to endocrine therapy (ET) in hormone-receptor-positive BC patients is active and voluntary for the first five years after diagnosis. This study examines the impact of adherence to ET on 10-year excess mortality (EM) in patients diagnosed with Stages I to III BC (N = 2297). Since sample size is an issue for estimating age- and stage-specific survival indicators, we developed a method, ComSynSurData, for generating a large synthetic data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 50 publications
0
6
1
Order By: Relevance
“…The cohort did not show a significantly higher risk of death from colon cancer, the second cause of cancer death, compared to the general population, but the increasing risks of developing this cancer in Spanish women aged 65 and older [52] (second tumour in the ranking of cancer incidence in Catalonia in women aged 74 and older), together with the good survival prospects of BC [15], are factors suggestive of an elevated future risk of colorectal incidence in our cohort. In contrast, the downward trend for risk of death due to leukaemia and haematological malignancies detected in our previous study [12] is consistent with our current results, since these tumours showed a non-significant risk relative to the general population.…”
Section: Cancer Causescontrasting
confidence: 59%
See 4 more Smart Citations
“…The cohort did not show a significantly higher risk of death from colon cancer, the second cause of cancer death, compared to the general population, but the increasing risks of developing this cancer in Spanish women aged 65 and older [52] (second tumour in the ranking of cancer incidence in Catalonia in women aged 74 and older), together with the good survival prospects of BC [15], are factors suggestive of an elevated future risk of colorectal incidence in our cohort. In contrast, the downward trend for risk of death due to leukaemia and haematological malignancies detected in our previous study [12] is consistent with our current results, since these tumours showed a non-significant risk relative to the general population.…”
Section: Cancer Causescontrasting
confidence: 59%
“…Treatment for HER2+ BCs includes chemotherapy plus HER2-targeted antibodies or small-molecule inhibitor therapy, whereas triple-negative tumours receive chemotherapy alone [6,7]. In this line, in a previous study, we found no excess mortality in HR+ patients diagnosed beyond 49 years of age at Stage I or beyond 59 years at Stage II if they followed the prescribed endocrine treatment regimen [15]. As survival of BC improves, there is an increased interest in the long-term outcomes in these patients, including their cause-specific probabilities of death [15,16].…”
Section: Introductionmentioning
confidence: 52%
See 3 more Smart Citations